Social Human-Robot Interaction for Gait Rehabilitation (2020)
Robot-assisted therapy for gait rehabilitation of patients with neurological disorders usually combines a body weight support system with a treadmill system. Lokomatis oneof the most useddevicesforgait rehabilitation. This device allows therapists to focus on the patient and the therapy. However, this therapy session is based on multi-tasking processes, which are often difficult for a therapist to manage. In this work, a Socially Assistive Robot (SAR) was integrated into a neurorehabilitation programasacollaboratoragenttopromotepatientengagement and performance during the therapy. This short-term study presents the effects comparing the social robot condition and control condition with a group of four neurological patients using repeated measurementdesign. As a remarkable result, patients improved thoracic 18.44% and cervical 32.23%postureonaveragewithSARassistance.Thisstudy demonstrated the feasibility of the integration of a social robot as a complement of gait rehabilitation programs.